PERCEPTION OF VISUAL AND THERMAL COMFORT IN WORKING AREA - Kristanto, Luciana; Oentoro, Sherine Monica (Lakar: Jurnal Arsitektur, 2024)
Visual comfort and thermal comfort can influence an activity. When carrying out activities, it is very necessary, especially these 3 (three) things, namely: Adequate lighting, a room that is free from glare, the need of seeing outside (view), and an appropriate room temperature. Each person's visual comfort can be different due to differences in perception. Each person's perception will be different depending on their experiences, beliefs and values. This research was carried out by distributing several questions on Google Form. This survey will compare 3 (three) types of second skin facades to be compared, namely: plant facades, horizontal lattice facades, and perforated metal facades, and then which of the three types is considered to provide the most visual and thermal comfort. The results obtained state that human perception of plant facades can provide visual and thermal comfort with 55.9% of respondents stating that plant facades are the best solution for obtaining visual comfort and 88.1% stating that plant facades are able to provide good thermal comfort. Respondents believe this is because plant facades can absorb sunlight, block sunlight consistently, and can provide oxygen, making the room become more fresh and cooler.